Durian Rind-Based Liquid Smoke as a Natural Preservative for Chicken Meatballs: Effect of Pyrolysis Temperature and Liquid Smoke Concentration - Muhammad Faisal; Suraiya Kamaruzzaman; Ressa Fitra Adinda; Dimas Anugerah Ilahi; Taufik Hidayat; Hera Desvita (Journal of Applied Engineering and Technological Science (JAETS), 2024)
Liquid smoke is produced by the pyrolysis of biomass.  The use of liquid smoke has numerous advantages over traditional smoking methods. The liquid smoke market is well-established and growing, providing an opportunity to commercialize biomass pyrolysis. This study aimed to investigate the utility of durian rind, biomass waste rich in lignin, cellulose, and hemicellulose, as a natural preservative to extend the shelf life of chicken meatballs and to mitigate environmental problems caused by the disposal of untreated durian rind waste. Dried durian rinds with approximately 10% water content were pyrolyzed at temperatures of 300°C (T1 liquid smoke), 340°C (T2 liquid smoke), and 380°C (T3 liquid smoke) using a slow pyrolysis reactor in batch conditions to produce crude liquid smoke, which was then purified by distillation at 190°C. Chicken meatballs were then soaked in liquid smoke solutions with concentrations of 1%, 2%, and 3% for 15 minutes, and the meatballs checked for signs of spoilage every 4 hours. Tests for total volatile base nitrogen (TVB-N), in addition to the total plate count (TPC) and most probable number (MPN) of Escherichia coli bacteria, were performed to evaluate the preservation ability of the liquid smoke. The results indicated that both the pyrolysis temperature and liquid smoke concentration affected the preservation time, with a pyrolysis temperature of T3 and liquid smoke concentration of 3% optimum for chicken meatball preservation. Under these conditions, the meatballs could be stored for 56 hours with TVB-N, TPC, and E. coli MPN values of 21.01 mg N/100 g, 5.37 × 104 CFU/g, and 75 MPN/g, respectively. The findings suggest that liquid smoke derived from durian rinds could be used to preserve chicken meatballs.